Emerging Protein Sources for Food Production and Human Nutrition (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The scope of this reprint, entitled “Emerging Protein Sources for Food Production and Human Nutrition”, encompasses the latest advancements in analytics and the application of new methods in the processing of proteins, both plant and animal, as well as methods of producing and testing foods enriched with these proteins.